Os significados do trabalho para doentes renais crônicos em tratamento de hemodiálise que mantêm a vida laboral - Cruz, Vera Fontoura Egg Schier da (2013)
Chronic kidney disease is characterized by impairment of functions such as filtering waste, regulation of water and other chemicals and the production of hormones. The hemodialysis as renal replacement therapy used for chronic renal failure patients is highlighted in the literature as a modality and imposes limitations suffered physical, psychological and social. Among the various aspects that change the lives of kidney patients, the work is described as one of suffering profound consequences in its continuity, and modifying the daily routine of the 7 patient, although it is not immediately incapacitated for work activities under varying conditions physical each, often need to resort to social benefits such as sick pay or disability retirement. This research aimed to understand, using as a basis the theoretical socio-historical psychology, meaning that kidney patients who use this treatment modality and remain in working life, ascribe to the work. Specific objectives were also searched the grounds for maintenance work and if it helps in fighting the disease. This methodology for conducting this scientific research was qualitative, using for data collection semistructured interviews focusing on life story work-related, the experience of illness and work, and participant observation. The survey sample was seven people (one woman and six men), aged between 32 and 85, who make use of hemodialysis as a method of treatment of renal failure, in clinical specialty in Curitiba/PR, and sustain life labor. The results of the meanings of work and the reasons for its maintenance pointed to the subsistence and consumerism, dignity/independence, the preservation of mental and maintenance activity at work and the identity of the worker. Among the respondents there was recognition of the work as beneficial for coping with the disease and treatment.